Moojenina: Nova enzima coagulante isolada da peçonha de Bothrops moojeni - Purificação e Caracterização - Morais, Nadia Cristina Gomes de (2011)
CHAPTER 2: A fibrinogenolytic metalloproteinase from Bothrops moojeni venom, named Moojenin, was purified by a combination of ion-exchange chromatography on DEAE-Sephacel and gel filtration on Sephacryl S-300. SDS-PAGE analysis indicated that Moojenin consists of a single polypeptide chain and had a molecular mass of about 45 kDa, under reducing conditions and 30 kDa, under non-reducing conditions. The N-terminal sequence of Moojenin was determined to be LGPDIVSPPVCGNELLEV and it showed identity with many other snake venom metalloproteinases. The enzyme cleaves the Aα-chain of fibrinogen first, followed by the Bβ-chain, and shows no effects on the γ-chain. Moojenin showed coagulant activity on bovine plasma about 3.1 fold lower than crude venom. The fibrinogenolytic activity of Moojenin was abolished by preincubation with EDTA, 1,10-phenanthroline and β-mercaptoethanol, which also inhibited the coagulant activity. The coagulant activity was also inhibited by benzamidine and leupeptin. Moojenin showed maximum activity from 30 to 40 °C and the optimal pH was 4. Its activity was completely lost at temperatures above 50 °C. Moojenin caused relevant morphological alterations in liver and muscle, but it did not cause histological alterations in the lung, kidney and heart of mice. Moojenin rendered the blood uncoagulable when it was intraperitoneally administered to mice. Moojenin may be of medical interest because its anticoagulant activity can be explored for the prevention and treatment of a wide range of thrombotic disorders.